Angola's planned and unplanned urban growth: diamond mining towns in the Lunda Provinces - Rodrigues, C. U.; Tavares, A. P. (Journal of Contemporary African Studies, 2012)
Mining towns in Angola have followed a different growth trajectory from urban agglomerations elsewhere on the continent. Colonial mining cities were treated as regional strategic locations mainly under the direction of mining companies, with an orientation towards natural and human resources management and planned urbanisation. As Angola became engulfed in civil war after independence in 1975, urban planning and control fell into disarray, which led to rapid and unplanned urban growth as rural populations fled the insecurity of the countryside. In the provinces of Lunda Norte and Lunda Sul, where diamond mining dominates economic activity, new ‘unplanned’ clandestine towns appeared during the civil war. Since the advent of peace in 2002 and the cessation of war-induced urbanisation, Lundas' towns have resumed their status of government and mining company-dominated settlements, where control and planning prevail. However, improved infrastructural conditions prevail alongside new forms of social and economic exclusion. This article traces urban growth and welfare in Lunda, analysing the impact of its divergent growth pattern on the urban population.